Psychological Stress Resulting from Distance Education Among Parents of Students with Learning Disabilities During the Covid-19 Pandemic - Mohammed Ali Mohammed Alamri (Journal La Edusci, 2021)
This study aimed at identifying the impact of psychological stress resulting from remote education among parents of students with learning disabilities during the Covid-19 pandemic. The study used the descriptive-analytical approach and a questionnaire as an instrument to achieve the objectives of the study. The instrument was administered to a sample consisting of (61) parents of students with learning disabilities, who were selected randomly. The results of the study showed that the level of stress was high among parents. The findings also showed that there were no statistically significant differences in the evaluation of the respondents about psychological stress resulting from education due to the variable of gender and educational level of the parents. The study recommended providing educational means for parents on how to deal with the psychological pressures they are experiencing in light of the continuation of distance education during the pandemic of the new Coronavirus (Covid-19) and finding alternatives for children to spend their time in useful ways during periods of home quarantine due to the pandemic.